Implementasi Budaya Total Quality Management (TQM) Dalam Meningkatkan Kualitas Pelayanan Purna Jual PT Autolift Karya Inovasi - Debri Ton Mario Hutasoit; Muhammad Rizki Aulia (Journal of Innovative and Creativity (Joecy), 2026)
After-sales service quality is a strategic factor in maintaining customer loyalty within a company. The implementation of a Total Quality Management (TQM) culture is widely recognized as an effective approach to improving service performance through customer orientation, employee involvement, standardized process management, and continuous improvement. This study aims to analyze the implementation of a TQM culture in enhancing the quality of after-sales services at PT Autolift Karya Inovasi in Medan City. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews with management personnel, technicians, administrative staff, and corporate customers, and were complemented by observations and document analysis. Data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing, while triangulation techniques were applied to ensure the credibility of the findings. The results indicate that the implementation of the TQM culture has been relatively effective. Customer focus is reflected in the established response-time standards for handling customer complaints, while cross-functional collaboration among administrative staff, technicians, and spare parts personnel has improved service coordination. In addition, the implementation of standardized operating procedures has contributed to consistent service quality, and continuous improvement has been supported through periodic evaluations of service performance. Nevertheless, the study also reveals that delays in spare parts distribution and variations in response times across customer locations remain significant challenges in maintaining consistent service quality. This study provides empirical evidence regarding the implementation of TQM in a technical distribution company operating in the Business-to-Business (B2B) market and offers managerial recommendations to enhance after-sales service effectiveness through strengthened cross-departmental coordination, optimized spare parts inventory management, and the development of a real-time service monitoring system..